The unknown shore - O'Brian, Patrick 1914-2000 (Norton, 1995)
In the 18th Century, a Royal Navy ship runs aground during a storm while on a mission to harass Spanish vessels off the coast of South America. A mutiny breaks out and the novel follows two young sailors as they battle the elements and fellow sailors to survive. By the author of The Golden Ocean.
Keywords: Geschichte 1700-1800; Shipwrecks -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Schiffbruch; Überleben; Großbritannien; Great Britain -- History, Naval -- 18th century -- Fiction; South America -- Fiction; Pazifischer Ozean; Südamerika; Fiktionale Darstellung; Historical fiction; Sea stories